2000
DOI: 10.1002/(sici)1096-8628(20000207)96:1<69::aid-ajmg14>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Peek-a-boo fragile site at 16d associated with Tourette syndrome, bipolar disorder, autistic disorder, and mental retardation

Abstract: Five patients with a fragile site at 16q22-23 and neuropsychiatric disorders are reported. Three of five had Tourette disorder, three had mental retardation, two had bipolar disorder, and one had autistic disorder. During our attempts to study the fragile sites in more detail we were unable to reproduce the fragile sites found several years earlier. The potential relationship between the fragile sites and the neuropsychiatric disorders in these patients is discussed. Am. J. Med. Genet. (Neuropsychiatr. Genet.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, later it was demonstrated that this fragile site is distal from the haptoglobin gene whose deficiency is linked to IgA deficiency, suggesting that the IgA condition in the propositus was likely a coincidence (Simmers et al 1986). Fragility at 16q22 has since been implicated in a wide spectrum of neurological disorders (Demirhan et al 2006; Kerbeshian et al 2000) as well as in other conditions such as neutropenia (Glasser et al 2006; Tassano et al 2010) and cleft palate (Bettex et al 1998; Dunner et al 1983; Janiszewska-Olszowska et al 2013; McKenzie et al 2002). A recent study also reported elevated fragile site formation at 16q22.1 in an embryo from a couple who had difficulty achieving pregnancy and in the sperm from the father (Martorell et al 2014).…”
Section: 2 Early History Of Chromosome Fragile Site Discoveries Rementioning
confidence: 99%
“…However, later it was demonstrated that this fragile site is distal from the haptoglobin gene whose deficiency is linked to IgA deficiency, suggesting that the IgA condition in the propositus was likely a coincidence (Simmers et al 1986). Fragility at 16q22 has since been implicated in a wide spectrum of neurological disorders (Demirhan et al 2006; Kerbeshian et al 2000) as well as in other conditions such as neutropenia (Glasser et al 2006; Tassano et al 2010) and cleft palate (Bettex et al 1998; Dunner et al 1983; Janiszewska-Olszowska et al 2013; McKenzie et al 2002). A recent study also reported elevated fragile site formation at 16q22.1 in an embryo from a couple who had difficulty achieving pregnancy and in the sperm from the father (Martorell et al 2014).…”
Section: 2 Early History Of Chromosome Fragile Site Discoveries Rementioning
confidence: 99%
“…In addition to these case reports, Kerbeshian et al studied 205 GTS patients in the North Dakota GTS Surveillance Project, and 15 (7%) were found to have had comorbid BAD. The estimated risk of developing BAD in individuals with GTS was more than four times higher than that expected by chance, but it failed to reach statistical significance; males with GTS were at a greater risk for BAD than females [84][85][86][87][88][89]. These authors therefore suggest a relationship between GTS and BAD.…”
Section: Bad and Gtsmentioning
confidence: 99%
“…Tourette syndrome has also been diagnosed in three of five patients with a fragile site at 16q22-23. 39 Several variables have been proposed to explain the unsuccessful genome search, including problems defining the phenotype, inaccurate diagnostic assessment, improper ascertainment methods, and problems with genetic modeling and data analysis. 40,41 Since gene mapping with large kindreds has failed to identify a specific consistent abnormality, efforts have begun to evaluate genetically isolated populations.…”
Section: Geneticsmentioning
confidence: 99%